Upstream and downstream explanations of the harms of ultra-processed foods in national dietary guidelines - Quinn, Madalyn; Jordan, Helen; Lacy-Nichols, Jennifer (Public health nutrition, 2021)
Dietary advice about the potential health risks of unhealthy foods or diets has historically been communicated in terms of nutrients. Recent evidence has shown that the processing of food itself is independently attributable to harmful outcomes, particularly a new category of foods described to be 'ultra-processed'. Dietary guidelines (DG) are a key policy tool to translate and communicate nutrition research; however, there is little research exploring whether and how the harms of food processing are communicated and rationalised in dietary advice. Nineteen publicly available DG were thematically analysed to explore: (1) the diversity of terms used to refer to processed foods and (2) the underlying explanations and rationales provided to reduce consumption of processed foods. International. Sample of national dietary guidelines. Seventeen different descriptive terms were used to refer to processed foods, with many countries using a large variation of terms within their DG. Six rationales to reduce consumption of processed foods were identified, which were grouped into four overarching domains: harmful outcomes (disease risk, environmental risk); food quality (food quality, nutrient content); diet quality and food environment. The rationales provided to reduce the consumption of processed foods reflect upstream and downstream determinants of health. However, the persistence of nutrient-based rationales indicate that most DG do not apply an upstream understanding of the issues with ultra-processing. Further, the diversity of terms and foods referenced in DG suggest that the concept of ultra-processing is subject to multiple interpretations.